2016
DOI: 10.3758/s13421-016-0641-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the testing effect under blocked and mixed practice: The mnemonic benefits of retrieval practice are not affected by practice format

Abstract: The act of retrieving information modifies memory in critical ways. In particular, testing-effect studies have demonstrated that retrieval practice (compared to restudy or to no testing) benefits long-term retention and protects from retroactive interference. Although such testing effects have previously been demonstrated in both between-and within-subjects manipulations of retrieval practice, it is less clear whether one or the other testing format is most beneficial on a final test. In two paired-associate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 62 publications
4
24
0
Order By: Relevance
“…In contrast, Pan and colleagues (2015) randomly mixed restudy and retrieval trials, which allowed for the possibility of carry over effects. Abel and Roediger (2017) however, have shown that the testing effect is equivalent across blocked and intermixed restudy. In the present study, participants were randomly assigned to complete either restudy first (n = 101) or practice retrieval first (n = 99).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, Pan and colleagues (2015) randomly mixed restudy and retrieval trials, which allowed for the possibility of carry over effects. Abel and Roediger (2017) however, have shown that the testing effect is equivalent across blocked and intermixed restudy. In the present study, participants were randomly assigned to complete either restudy first (n = 101) or practice retrieval first (n = 99).…”
Section: Methodsmentioning
confidence: 93%
“…Although this delay differs from the previous studies, empirical results have shown that delays longer than 5 mins show a testing effect whereas some studies with delays under 5 minutes show an advantage for restudying (Roediger & Karpicke, 2006;Roediger & Butler 2011). Additionally, Carpenter et al, (2008, study 1) compared delays of 5 mins, 1 day, 2 days, 1 week, 2 weeks, or 42 days, and found no interaction between the testing effect and retrieval interval and testing effects were present at all delays (also see Able & Roediger, 2017;Avci et al, 2017). At final test participants completed self-paced cued recall of all 40 word pairs.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Others report that the option to retake exams lowers students' test anxiety and leads to higher student satisfaction with the course and instruction overall (Carey 2014;Brown et al, 2014). Hence, a growing body of evidence suggests the testing effect, enabled via a test-retest pedagogy, improves student's knowledge acquisition, classification, and retention (Butler et al, 2007;Roediger et al, 2011;Dirkx et al, 2014;Abel & Roediger, 2016, Batsell, Perry, Hanley, & Hostetter, 2017. Improving familiarity, progressive mastery via improving metacognitive accuracy, as well as processes of "test-potentiated learning," in turn, reportedly diminish a student's test anxiety (Brown et al, 2014).…”
Section: Interactionmentioning
confidence: 99%
“…In general, repeated testing benefits the test-taker by improving knowledge acquisition, classification, and retention (Butler et al, 2007;Karpicke, 2009;Dirkx et al, 2014;Agarwal et al, 2014;Abel & Roediger, 2016, Batsell, et al, 2017. The instrumentality of the testing effect, by offering a student a series of low-stress assessments, enables him or her to translate growing competency-based experience into the self-confidence that reduces, if not neutralizes, performance anxiety (Hembree, 1988;Ergene, 2003;Carey, 2014;Brown et al, 2014).…”
Section: Diminishing Deficiencies and Reducing Anxietymentioning
confidence: 99%